JUAL BELI SUBSCRIBERS YOUTUBE PERSPEKTIF HUKUM ISLAM - SIRAIT, ADI SYAHPUTRA; Tanjung, Dhiauddin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This article aims to explain whether Subscribers and Viewers are part of the property and how the law of buying and selling is from the perspective of Islamic Law. The method used in this paper is normative empirical with a phenomenological approach. The technique used in collecting data in this article is by observing and tracing the buying and selling practices of viewers and subscribers in online buying and selling services. Then the data is analyzed using literature related to buying and selling (Fiqh Muamalah). The results of this study indicate that the sale and purchase of viewers and subscribers is the sale and purchase of tadlis which is prohibited in Islam because it contains elements of Gharar (uncertainty) both in the account sold by the seller because it is not owned or the benefits received by the buyer because it can decrease at any time. Meanwhile, viewer and subscriber buying and selling transactions that are permitted according to syara' law are carried out using aqad istisna' provided that the account is not for commercial use.